Fibromyalgia: Moderate and substantial pain intensity reduction predicts improvement in other outcomes and substantial quality of life gain. - Moore, R; Straube, S; Paine, J; Phillips, C; Derry, S; McQuay, H (2010)
Chronic pain is associated with a range of other problems, including disturbed sleep, depression, anxiety, fatigue, reduced quality of life, and an inability to work or socialise. We investigated whether good symptom control of pain (using definitions of moderate and substantial benefit) is associated with improvement in other symptoms. Individual patient data from four randomised trials in fibromyalgia (2575 patients) lasting 8-14weeks were used to calculate percentage pain reduction for each completing patient (1858), divided into one of five groups according to pain reduction, irrespective of treatment: substantial benefit - 50% pain reduction; moderate - 30% to <50%; minimal - 15% to <30%; marginal - 0% to <15%; worse - <0% (increased pain intensity). We then calculated change from baseline to end of trial for measures of fatigue, function, sleep, depression, anxiety, ability to work, general health status, and quality-adjusted life year (QALY) gain over a 12-month period. Substantial and moderate pain intensity reductions were associated with statistically significant reduction from baseline by end of trial in all measures, with values by trial end at or approaching normative values. Substantial pain intensity reduction resulted in 0.11 QALYs gained, and moderate pain intensity reduction in 0.07 QALYs gained over a 12-month period. Substantial and moderate pain intensity reduction predicts broad beneficial outcomes and improved quality of life that do not occur without pain relief. Pain intensity reduction is a simple and effective predictor of which patients should continue treatment, and which should discontinue and try an alternative therapy.